2002
DOI: 10.1093/jurban/79.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the AIDS Epidemic Among New York City's Injection Drug Users: Localized or Citywide?

Abstract: The New York City injection drug user acquired immunodeficiency syndrome (IDU AIDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…The decrease in rates of diagnoses among blacks during 2001-2004 was driven, in part, by decreases in New York, which might be attributed to the New York epidemic being older than the epidemic in some other areas of the United States, the volume of cases reported into the system, and recent changes in reporting requirements. ‡ Decreases in HIV diagnoses among IDUs were consistent with other re-ports of success in reducing HIV incidence among IDUs 6 and might account, in part, for decreases observed among blacks. However, rates among blacks have remained high and warrant increased prevention efforts, especially among black MSM and black women.…”
Section: From the Centers For Disease Control And Preventionsupporting
confidence: 80%
“…The decrease in rates of diagnoses among blacks during 2001-2004 was driven, in part, by decreases in New York, which might be attributed to the New York epidemic being older than the epidemic in some other areas of the United States, the volume of cases reported into the system, and recent changes in reporting requirements. ‡ Decreases in HIV diagnoses among IDUs were consistent with other re-ports of success in reducing HIV incidence among IDUs 6 and might account, in part, for decreases observed among blacks. However, rates among blacks have remained high and warrant increased prevention efforts, especially among black MSM and black women.…”
Section: From the Centers For Disease Control And Preventionsupporting
confidence: 80%
“…The relatively low prevalence of IDU may be due to the size of city or other social and health care factors (poverty, overcrowding, education, universal health care, access to needle exchange programs), however the relationship between such factors and the prevalence of IDU is uncertain. [25][26][27][28][29][30][31][32][33][34] The gender composition of our patients is not unexpected in a North American setting. All of the cases in the present study were male, compared with a range of 65-95% in other North American reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that blood-borne virus infections and high-risk injection behaviour among IDUs are not distributed homogeneously within city boundaries (Brugal et al, 2003;Diaz et al, 2001;Hutchinson et al, 2000;Maas et al, 2007;Miller et al, 2004;Rockwell et al, 2002;Wood et al, 2002). In comparison with their counterparts residing in less central surrounding areas, IDUs in the inner city of Barcelona, Spain, were more likely to be infected with HIV (Roca et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For IDUs as well as the average resident, a 10-minute walking distance, corresponding to a 500-meter buffer, is generally recognised as a reasonable radius by which to represent access to local services. (Cooper et al, 2008;Rockwell et al, 1999;Rockwell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%